ΤΟ ΔΗΜΟΤΙΚΟ ΤΡΑΓΟΥΔΙ ΑΠΟ ΤΟ ΠΛΑΙΣΙΟ ΤΗΣ ΠΑΡΑΔΟΣΙΑΚΗΣ ΚΟΙΝΟΤΗΤΑΣ ΣΤΗ ΘΕΑΤΡΙΚΗ ΣΚΗΝΗ: Η ΠΕΡΙΠΤΩΣΗ ΤΗΣ ΠΑΡΑΣΤΑΣΗΣ ΜΕ ΤΑ ΤΡΑΓΟΥΔΙΑ ΣΟΥ ΜΙΛΩ, ΘΕΑΤΡΟ ΑΛΦΑ ΙΔΕΑ ΑΘΗΝΩΝ [THE FOLK SONG FROM THE CONTEXT OF THE TRADITIONAL COMMUNITY TO THE THEATRE STAGE: THE CASE OF THE PERFORMANCE TALKING TO YOU WITH SONGS, ALPHA IDEA THEATRE, ATHENS] - Sdoukos, Panagiotis (ΠΑΡΑΒΑΣΙΣ/PARABASIS, 2025)
The folk song is deeply rooted in its historical and cultural context. It is considered an inexhaustible source of information regarding the cultural identity of non-urban, symbiotic, and rural communities. Moreover, as we will see next, the folk song a) serves as a foundation for musical-theatre performances and modern, artistic, educational programs, and b) inspires artists to integrate it into a new framework of action. This research aims to redefine the position of the folk song and its ritual acts as a «spectacle» within contemporary artistic productions, incorporating elements of dramatic performance on theatrical stages. Therefore, it proposes and analyzes the «performance in the micro-place» as a project of auto-ethnographic and artistic research, which a) combines Ethnomusicology with Performing Arts [interdisciplinary research and embodied & vocal performative practices], and b) involves the creation of new small [micro] workshops for the research, teaching, and performance of the folk song, ranging from a simple classroom to outdoor or artistic venues (nature, theatres, etc.). In the field, the ethnographer also interacts with his voice-body as a teacher and performer. In conclusion, through this research, «performance in the micro-place» follows the autoethnographic method to define the folk song as a holistic model of educational and artistic research and performance in new cultural environments.